Pembinaan Model Kaunseling Kepimpinan (M-KKEP) dalam kalangan pengetua di Maktab Rendah Sains Mara - Mohd Shahid, Ahmad (2025)
The counselling approach is relevant to be practiced by school principals in ensuring the school’s vision and mission are realized. However, the counselling element is still given little attention in the leadership model of principals at MARA Junior Science Colleges. Therefore, this study aims to develop and validate the Leadership Counselling Model (M-KKEP) among principals at Maktab Rendah Sains MARA. This study involves three phases: 282 respondents in the need analysis phase, 13 field experts in the model design phase, and 213 respondents in the final model evaluation phase. The study uses a questionnaire adapted from the McEwan-Adkins Instructional Leadership Feedback Checklist and basic counselling skills based on Corey’s perspective. To validate the model constructs, the study findings were analysed using PLS-SEM. The findings of the study indicate that eight constructs have been established, namely: counselling skills, professional leadership, concern, therapeutic work environment, developing leadership among principals, leaders as drivers of change, leaders in setting organizational goals, and entrepreneurial values in educational leadership. This study developed a principal leadership model that integrates elements of counselling and leadership. Furthermore, this study can assist MARA in enhancing the quality of leadership among principals of MRSM through the M-KKEP Model.